The Epidermiology of Hairstyle related african hair disdorders, in and Urban Township in South Africa - Khumalo, Nonhlanhla P (Division of Dermatology, 2014)
The hair of indigenous people of Africa varies from the north to the south of the continent. Although the variation in hair colour from light brown to black occurs, the most significant difference is in the curls which are tightest, and spiral, in indigenous sub Saharan Africans. African hair for the purpose of this thesis refers to the latter hair phenotype. The unique morphology of this hair type is associated with specific responses to grooming. In addition hairstyle preferences may be influenced by politics and fashion. Specific scalp disorders have been anecdotally reported to be more prevalent in Africans. These are acne (folliculitis) keloidalis (AKN), central centrifugal cicatricial alopecia (CCCA) and traction alopecia (TA). For many years all these conditions have been suspected to have a causal association with hairstyles. However, preliminary investigation suggested a lack of population studies demonstrating the latter association. In addition the possible influence of the unique African hair follicle on disease pathogenesis had not been determined. The aims of this thesis were to: Present a systematic 1. literature review of published prevalence and incidence data on the above three conditions. 2. Conduct cross sectional studies to investigate the prevalence of AKN, CCCA and TA in a population of school children and adults and the prevalence of different hairstyles, and to describe any associations between hairstyles and disease. 3. Develop and test for reliability a new severity scoring system for TA the commonest of the above conditions [the marginal traction alopecia severity (M-TAS) scoring instrument]. 4. Evaluate the determinants of both TA presence and severity in African females using data from our cross sectional studies in school children and adults.